2018
DOI: 10.35762/aer.2018.40.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Sustainability of Accra Metropolitan Area, Ghana

Abstract: Cities have become integral in the quest to achieving universal sustainable development. For example, the United Nations in 2015 as part of the 17 Sustainable Development Goals called for cities and human settlements to be inclusive, safe, resilient and sustainable (Goal 11). This was in line with the 2012 National Urban Policy of Ghana which seeks to promote a sustainable, spatially integrated and orderly development of urban settlements with adequate housing, infra-structure and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Generally, the young (typically defined as those under 15) consume less and are less engaged in production activities than the rest of the population; hence, a higher proportion of adults in a population may increase impact even as it enhances economic growth (Bloom and Canning, 2003; York et al , 2003). Urbanization, especially when based on rural-to-urban migration, is likely to produce changes in lifestyle and consumption patterns that might increase environmental impact (Earnhardt-Martinez, 1998; Cobbinah et al , 2017; Aryee et al , 2018).…”
Section: Ecological Footprint Of a Newly Developing Local Region: A C...mentioning
confidence: 99%
“…Generally, the young (typically defined as those under 15) consume less and are less engaged in production activities than the rest of the population; hence, a higher proportion of adults in a population may increase impact even as it enhances economic growth (Bloom and Canning, 2003; York et al , 2003). Urbanization, especially when based on rural-to-urban migration, is likely to produce changes in lifestyle and consumption patterns that might increase environmental impact (Earnhardt-Martinez, 1998; Cobbinah et al , 2017; Aryee et al , 2018).…”
Section: Ecological Footprint Of a Newly Developing Local Region: A C...mentioning
confidence: 99%
“…The World Bank (2015) also indicated that governmental reforms for sustainable cities cannot be effective without a planning system with a greater degree of inclusiveness and equity in the planning process. According to Aryee et al (2018), a sustained urban development “is the coordination of socio-economic and environmental management goals by systems of government to bring forth long-term growth and progress characterized by efficient use of resources, clean environment, healthy people, justice, and equal opportunities” (p. 28). Yet, challenges to building and maintaining sustainable cities include pollution, poor waste management and the degradation of green areas; most of these challenges in Ghana can be attributed to rapid urbanization, poor urban planning and resulting poverty (Cobbinah et al , 2017).…”
Section: Ghana At the Macro-levelmentioning
confidence: 99%
“…The lax enforcement of land-use planning regulations has led to the growth of unregulated buildings and waste management problems in the cities in Ghana (Aryee et al 2018). The status of waste management is unimpressive (See Fig.…”
Section: Land-use and Urban Planning Systemmentioning
confidence: 99%